An Education Program for Patient Self-Management of Warfarin - Jenner, Kathleen M (Perm J, 2015)
INTRODUCTION: Although improved anticoagulation therapy outcomes have been demonstrated in clinical trials evaluating warfarin patient self-management (PSM) programs, these studies did not provide detailed information regarding PSM program development and patient training. OBJECTIVE: To evaluate the feasibility of and methods for developing and administering an education program to support a novel pilot warfarin PSM program. METHODS: Patients receiving warfarin for atrial fibrillation were recruited to participate in a prospective, intervention-only, open-label pilot PSM program that released venipuncture international normalized ratio results to patients via a secure, online Web site. To support the pilot, a warfarin PSM education program with a dosing algorithm was developed and delivered to patients during a two-hour classroom session. MAIN OUTCOME MEASURE: A comparison of participants’ PSM competency test scores before and after attending the PSM program. RESULTS: Forty-four patients attended the education program. The mean age of participants was 71 years and 50% were women. Patients declining study participation were older (p = 0.003) and had a greater burden of chronic disease (p = 0.005) than participants. Following PSM training, the mean competency score improved from 55.8% to 88.8% (p < 0.001), and the proportion achieving a passing score increased from 34.9% to 95.3% (p < 0.001). In the poststudy survey, 100% of responders perceived that PSM training prepared them to self-manage warfarin, and 92.9% of responders were comfortable changing warfarin doses on their own. CONCLUSION: Developing and administering a warfarin PSM education program for patients with atrial fibrillation was feasible. Improvement in PSM competency and high levels of self-reported comfort with warfarin PSM were identified.